Pressure-induced insulator–metal transition in EuMnO3. (21st June 2017) - Qiu, R; Bousquet, E; Cano, A
Abstract: We study the influence of external pressure on the electronic and magnetic structure of EuMnO3 from first-principles calculations. We find a pressure-induced insulator–metal transition at which the magnetic order changes from A -type antiferromagnetic to ferromagnetic with a strong interplay with Jahn–Teller distortions. In addition, we find that the non-centrosymmetric E * -type antiferromagnetic order can become nearly degenerate with the ferromagnetic ground state in the high-pressure metallic state. This situation can be exploited to promote a magnetically-driven realization of a non-centrosymmetric (ferroelectric-like) metal.